Proactive Financial Reporting Enforcement: Audit Fees and Financial Reporting Quality Effects - Florou, Annita; Morricone, Serena; Pope, Peter F. (The Accounting Review, 2020)
ABSTRACT We examine the costs and benefits of proactive financial reporting enforcement by the U.K. Financial Reporting Review Panel. Enforcement scrutiny is selective and varies by sector and over time, yet can be anticipated by auditors and companies. We find evidence that increased enforcement intensity leads to temporary increases in audit fees and more conservative accruals. However, cross-sectional analysis across market segments reveals that audit fees increase primarily in the less-regulated AIM segment, and especially those AIM companies with a higher likelihood of financial distress and less stringent governance. On the contrary, less reliable operating asset-related accruals are more conservative in the Main segment and, in particular, those Main companies with stronger incentives for higher financial reporting quality. Overall, our study indicates that financial reporting enforcement generates costs and benefits, but not always for the same companies. JEL Classifications: K42; M41; M42; M48. Data Availability: Data are available from the public sources cited in the text.